2006
DOI: 10.1243/13506501jet168
|View full text |Cite
|
Sign up to set email alerts
|

‘Inlet suction’, a load support mechanism in non-convergent, pocketed, hydrodynamic bearings

Abstract: It is shown that a simple parallel pad bearing containing a closed pocket can support load if it operates in an ambient pressure that is appreciably in excess of the cavitation pressure of the lubricating fluid. This arises due to fluid flow driven by subambient pressures in the inlet region of the pad (‘inlet suction’). Maximum load capacity occurs when the pocket is located near the inlet to the bearing and under conditions such that cavitation is just provoked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
72
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 6 publications
8
72
1
Order By: Relevance
“…In these two papers it was clearly shown that load support is over predicted and friction coefficient under-predicted when a non-mass conserving formulation is applied. This criticism has been supported by previous contributions of the current authors [10,11], in which a semi analytical mass-conserving formulation of the Reynolds equation including the effects of cavitation was used to show that the critical pressure enhancement in textured bearings occurs downstream of the cavitation reformation boundary and is therefore critically affected by the boundary conditions in the reformation zone. A mass conserving algorithm was identified as key in correctly predicting bearing performance.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In these two papers it was clearly shown that load support is over predicted and friction coefficient under-predicted when a non-mass conserving formulation is applied. This criticism has been supported by previous contributions of the current authors [10,11], in which a semi analytical mass-conserving formulation of the Reynolds equation including the effects of cavitation was used to show that the critical pressure enhancement in textured bearings occurs downstream of the cavitation reformation boundary and is therefore critically affected by the boundary conditions in the reformation zone. A mass conserving algorithm was identified as key in correctly predicting bearing performance.…”
Section: Introductionmentioning
confidence: 89%
“…This is particularly true in cases where cavitation and reformation may occur multiple times within the computational domain of interest (e.g. rough contacts [28], textured surfaces [8,10,11,[29][30][31] and dynamically loaded journal bearings [9,16]). …”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, researchers at Imperial College compared the performance of a wide range of texture geometries, under various operating scenarios, in both experimental and theoretical studies [5][6][7][8][9][10]. Recently, the group's experiments showed that, under reciprocating piston-liner type conditions, beneficial or detrimental effects of surface texture could be achieved depending on which lubrication regime the contact operated under [9].…”
Section: Introductionmentioning
confidence: 99%
“…If cavitation occurs in the divergent zone at a pressure lower than the ambient pressure, the pressure difference between the surroundings and the cavitation zone generates a Poiseuille flow that introduces the lubricant into the lubricated area. This is the basic concept underlying the inlet suction suggested by Olver and colleagues [13][14][15]. A lower cavitation pressure generates a stronger Poiseuille flow, inducing a higher pressure in the convergent zone of the dimple, as shown in Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Olver et al [13] suggested that cavitation occurring in a single pocket located on the leading side of pad bearings generates a Poiseuille flow; this phenomenon has been termed "inlet suction." This Poiseuille flow introduces more lubricant into the lubricated area, resulting in an increased load-carrying capacity.…”
Section: Introductionmentioning
confidence: 99%